2023
DOI: 10.1139/cjm-2022-0147
|View full text |Cite
|
Sign up to set email alerts
|

Marine-derived antimicrobial molecules from the sponges and their associated bacteria

Abstract: Antimicrobial resistance (AMR) is one of the leading global health issues that demand urgent attention. Very soon the world will have to bear the consequences of increased drug resistance if new anti-infectives aren't pumped into the clinical pipeline in a short period. This presses on the need for novel chemical entities, and the marine environment is one such hotspot to look for. The Ocean harbours a variety of organisms, of which from this aspect, "Sponges (Phylum Porifera)" are of particular interest. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 148 publications
0
4
0
Order By: Relevance
“…Out of a total of 31 clinical isolates tested, 10 were AMI-R (Mabs = 5 and MAC = 5 (Mav = 2, Mint = 3)), 9 isolates were resistant to CLA (Mabs = 7, Mav = 2), and 6 strains were resistant to both CLA and AMI (Mabs = 4 and MAC = 2 (Mav = 1, Mint = 1)) that inhibit protein synthesis machinery. Most of the peptides or thiopeptides like NF1001 exert their antibacterial activity via the inhibition of ribosomal protein synthesis [45,46]. The potent activity of NF1001 against clinical isolates of NTM resistant to the protein synthesis inhibitors (AMI and CLA) clearly indicates a novel mechanism distinct from AMI and CLA.…”
Section: Discussionmentioning
confidence: 99%
“…Out of a total of 31 clinical isolates tested, 10 were AMI-R (Mabs = 5 and MAC = 5 (Mav = 2, Mint = 3)), 9 isolates were resistant to CLA (Mabs = 7, Mav = 2), and 6 strains were resistant to both CLA and AMI (Mabs = 4 and MAC = 2 (Mav = 1, Mint = 1)) that inhibit protein synthesis machinery. Most of the peptides or thiopeptides like NF1001 exert their antibacterial activity via the inhibition of ribosomal protein synthesis [45,46]. The potent activity of NF1001 against clinical isolates of NTM resistant to the protein synthesis inhibitors (AMI and CLA) clearly indicates a novel mechanism distinct from AMI and CLA.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated hydrocarbon components contained in the CTR sponge extract are suspected that these marine sponges most likely live or grow and reproduce in marine waters exposed to hydrocarbon pollutants [23], [26]. Sponges nourish these pollutants because sponges can convert carbon into energy for living activities [14], [16], [53]. Nourishing the carbon component causes these pollutants to enter the sponge's living metabolic system, eventually becoming a part or component forming the body structure of the sponge [19], [54].…”
Section: The Chemical Component Of the N-hexane Extract On Clathria (...mentioning
confidence: 99%
“…Previous research on this topic has reported that several marine animals, such as sea stars and sponges, have medicinal value [13], [14]. This can be seen in the antibacterial activity of the sponge extract against pathogenic bacteria and parasitic fungi, such as the ability to inhibit the growth of Staphylococcus aureus, Bacillus subtilis, Salmonella thypi, and Escherichia coli, Candida albicans [15], [16], [17]. The results of other studies also report that sponge extract can inhibit the growth of disease-causing enzymes; for example, it has Acetylcholinesterase activity, an enzyme that can lead to a weakening of the ability to think in humans [18], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation